Genes in sport and doping - Pokrywka, A.; Kaliszewski, P.; Majorczyk, E.; Zembron-Lacny, A. (Biology of Sport, 2013)
Genes control biological processes such as muscle production of energy, mitochondria biogenesis, bone formation erythropoiesis, angiogenesis, vasodilation, neurogenesis, etc. DNA profiling for athletes reveals genetic variations that may be associated with endurance ability, muscle performance and power exercise, tendon susceptibility to injuries and psychological aptitude. Already, over 200 genes relating to physical performance have been identified by several research groups. Athletes` genotyping is developing as a tool for the formulation of personalized training and nutritional programmes to optimize sport training as well as for the prediction of exercise-related injuries. On the other hand, development of molecular technology and gene therapy creates a risk of non-therapeutic use of cells, genes and genetic elements to improve athletic performance. Therefore, the World Anti-Doping Agency decided to include prohibition of gene doping within their World Anti-Doping Code in 2003. In this review article, we will provide a current overview of genes for use in athletes` genotyping and gene doping possibilities, including their development and detection techniques.